The impact of cross-functional teams on lean practices : a look from emotional intelligence and its influence on innovation processes. (2020)
Purpose: This research aims to investigate the impact that cross-functional teams have on lean practices and how they influence innovation processes within companies. The study seeks to examine these relationships taking “emotional intelligence” as the analysis’s central axis. Study Design: A self-administered questionnaire was designed and used to collect responses from 190 employees of different large companies with operations in Colombia and several countries worldwide. Main findings: Cross-functional teams are the main factors for companies to achieve long-term profitability. Their use and adaptation in the companies of the region would mean an increase in their effectiveness of processes, innovation, and promotion of collaborative environment between work areas.